Laundry Service Website Using the Waterfall Method (Case Study: Jamri Sura Laundry, Southeast Aceh) - Syahrijal Alas Pagan; Sry Karmila; Rahma Darliani; Sanjaya Alacsel (Jurnal Armada Informatika, 2026)
Berkah Laundry is a clothing-care service business in Southeast Aceh Regency that still faces limitations in order recording, price information delivery, pickup and delivery coordination, and laundry status tracking. This study aims to develop an integrated service website that enables customers to submit orders while assisting managers in controlling transactions and production processes. The system was developed using the Waterfall method through requirements analysis, design, implementation, testing, and maintenance stages. Requirements were collected through service-process observation, manager interviews, and transaction-document analysis. The resulting responsive website provides service-package information, ordering, cost estimation, pickup and delivery scheduling, status tracking, payment recording, digital invoices, customer management, and operational reporting. Evaluation used 18 black-box scenarios and 30 simulated transactions. All scenarios produced the expected outputs, every order code remained unique, cost calculations for the simulated data were correct, and each status transition could be traced. Process modeling also reduced the main service flow from eight manual activities to five integrated activities. These results indicate that the website can improve data discipline, service transparency, and Berkah Laundry’s readiness to provide more consistent and measurable digital services.